Marketing Strategy for Fish Crackers with Creative Packaging Using Social Media at the Bumi Mangrove Group UMKM, Percut Village, Deli Serdang, North Sumatra - Elly Romy (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This service was held on Monday, March 10, 2025, in Percut Village. Percut District Will Be Old. Deli Serdang Regency. This service is carried out to overcome problems, meet the needs of the community, and develop the process of knowledge and social change of the mangrove earth group. Based on the results of the service, it can be concluded that a good strategy so that promotional and marketing activities can determine the success of a processed product. Because at this time there are many sellers of processed fish skin cracker products who compete in marketing their products. Therefore, this processed mackerel skin cracker product is from the Percut Village Mangrove Earth Group. Marketing and promoting their processed products through online media. Considering that currently along with the development of the times, technological sophistication (science and technology) also develops and makes Damai Jaya's processed business introduce through online media such as: Instagram, WhatsApp and FB. In addition, there are many things that must be considered in marketing and promoting a product, namely by determining product strategy, price strategy, and promotion and marketing strategies through online media. If all of these strategies are carried out properly, the success of a product will increase and one of them is by utilizing the sophistication of online media.